2016
DOI: 10.21577/0103-5053.20160283
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Elements and Microbiological Content of Food: Evidence from a Case Study in a Brazilian City Heavily Contaminated by Lead and Cadmium

Abstract: Food security has become a major concern of the world population and this is even more prominence in polluted areas. This study aimed to evaluate microbiological and toxic elements content of local food itens from Santo Amaro, Bahia. The determination of lead, cadmium, Escherichia coli (E. coli) and total coliform were carried out in coriander, cassava, okra, chicken muscle/liver, fish muscle and eggs. The population of total coliform and E. coli were estimated by the express count method using plates EC (AOAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Thus, the population of Santo Amaro could be affected when the food consumed presents bioaccumulative contaminants in the food chain, especially lead (Pb). The results of previous studies conducted by our research group showed that, among the foods (of plant and animal origin) produced in Santo Amaro and most consumed by the population, the highest levels of cadmium and lead were found in samples of chicken (Gallus gallus domesticus) muscle tissue and in the cassava (Manihot esculenta) (Macedo et al, 2016).…”
Section: Samplingmentioning
confidence: 65%
See 3 more Smart Citations
“…Thus, the population of Santo Amaro could be affected when the food consumed presents bioaccumulative contaminants in the food chain, especially lead (Pb). The results of previous studies conducted by our research group showed that, among the foods (of plant and animal origin) produced in Santo Amaro and most consumed by the population, the highest levels of cadmium and lead were found in samples of chicken (Gallus gallus domesticus) muscle tissue and in the cassava (Manihot esculenta) (Macedo et al, 2016).…”
Section: Samplingmentioning
confidence: 65%
“…According to Macedo et al (2016), who found high levels of lead in muscle tissue of chickens from Santo Amaro, the possible source of exposure for these animals was the contaminated soil, as well as the eating habits of these birds that scratch and peck at the ground. The association between eating habits and lead levels in the blood of different groups of birds was demonstrated by Garcia-Fernandez et al (1995) where it was revealed that omnivorous species (such as chickens) and scavengers showed higher levels of contamination by this toxic metal when compared to piscivorous and insectivorous birds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If good hygiene is not practiced, yoghurt, a dairy product commonly consumed in Sri Lanka, also gets contaminated with spoilage and pathogenic microorganisms. Presence of coliforms usually indicates failures in hygienic practices in food preparation and Escherichia coli indicates faecal contamination leading to possible food safety issues (Macedo et al, 2017). However, microbial quality of yoghurt greatly varies with the brand due to varying degree of best practices followed by the manufacturers.…”
Section: June 2021mentioning
confidence: 99%